Evaluation of pet owner preferences for operative sterilization techniques in female dogs within the veterinary community. (5th February 2018) - Hsueh, Christine; Giuffrida, Michelle; Mayhew, Philipp D.; Case, J. Brad; Singh, Ameet; Monnet, Eric; Holt, David E.; Cray, Megan; Curcillo, Chiara; Runge, Jeffrey J.
Abstract: Objective: To describe pet owner preferences within the veterinary community when choosing operative techniques for canine spay. Study Design: Prospective survey. Sample Population: 1234 respondents from 5 veterinary university teaching hospitals in North America. Methods: An electronic survey was distributed to faculty, students, and staff that currently are or previously were dog owners. Responses were analyzed to determine what spay technique respondents would choose for their own dogs. Surgical options offered included open celiotomy, 2‐port (TP) laparoscopy, single‐port (SP) laparoscopy, and natural orifice transluminal endoscopic surgery (NOTES). Results: TP laparoscopic ovariectomy (OVE) was the most popular choice, followed by SP laparoscopic OVE; NOTES was the least popular technique when all surgical options were available. If only minimally invasive surgeries were offered, 0.3% of respondents would refuse surgery. Nearly half (48%) of respondents were willing to spend between 100 and 200 more for a minimally invasive OVE than for an open celiotomy. Conclusion: Minimally invasive OVE is an acceptable operative approach to those in the veterinary community. Additional study is required to correlate these findings with the general veterinary client population.